2023
DOI: 10.7717/peerj.14288
|View full text |Cite
|
Sign up to set email alerts
|

Change and stasis of distinct sediment microbiomes across Port Everglades Inlet (PEI) and the adjacent coral reefs

Abstract: Deep water ports are human built coastal structures that by definition welcome ship traffic and disturbance. Evidence is accumulating that enhanced port activities such as dredging or deepening have negatively affected nearby natural habitats. Port Everglades Inlet (PEI) is a large active South Florida cargo port for over two million people and lies adjacent to coral reefs, dwindling mangroves, and recreational beaches. In this study, the microbial communities of PEI and adjacent reef sediments were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Finally, we showed that sediments collected near the Port contained higher abundances of potentially pathogenic bacteria compared to Reef sediments, aligning with previous work conducted in the vicinity of the Port Everglades inlet [65, 72]. These studies highlight the importance of monitoring for potential contaminants in sediments and changes in the microbiome which may result from dredging.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, we showed that sediments collected near the Port contained higher abundances of potentially pathogenic bacteria compared to Reef sediments, aligning with previous work conducted in the vicinity of the Port Everglades inlet [65, 72]. These studies highlight the importance of monitoring for potential contaminants in sediments and changes in the microbiome which may result from dredging.…”
Section: Discussionsupporting
confidence: 89%
“…Relative abundance analysis of the most abundant taxa showed that Desulfobacterales were unique to the Port sediments (Fig 3C). These taxa have been found to be enriched in microbial communities from other inlets in southeast Florida [65] and have also been associated with black band disease [66], suggesting that this bacterial taxa may play a role in coral health and its enrichment in Port sediments may have contributed to the reduced survival and settlement in larvae exposed to both low- and high-doses of these sediments (Fig 2A). Moreover, Desulfobacterales are anaerobic sulfate-reducing bacteria [67] that reduce sulfate (SO 4 2− ) to hydrogen sulfide (H 2 S).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative abundance analysis of the most abundant taxa showed that Desulfobacterales were unique to the Port sediments (Fig 3C). These taxa have been enriched in microbial communities from other inlets in southeast Florida [71] and have also been associated with black band disease [72], suggesting a role in coral health. Moreover, Desulfobacterales are anaerobic sulfate-reducing bacteria [73] that reduce sulfate (SO 4 2−…”
Section: Plos Onementioning
confidence: 99%
“…Sediments may also act as vectors for the transmission of diseases such as Stony Coral Tissue Loss Disease [22], first reported in outbreak levels (>5% prevalence) in waters of Miami-Dade County around September 2014 ( [76,77] but see [78,79]), while the Port of Miami expansion dredging project was underway. Also, bacteria genera from two common human pathogens, Staphylococcus and Streptococcus, have been found across multiple time points in surface water and sediment samples near Port Everglades [71,80], another southeast Florida inlet subject to dredging impacts. Our findings add to these studies and also suggest that port inlets may carry potentially pathogenic bacteria which may be transported to nearby reefs through various sediment transport processes (natural or anthropogenic), resulting in potential exposure to coral larvae and other downstream health impacts.…”
Section: Plos Onementioning
confidence: 99%